(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
The Pax Augusta is a motif that seems to follow the whole development of the new Augustean power. This work focuses on some relevant phases relating to the handling of this concept that appears to be strictly bound to the results of Augustus’ political and military deeds. In this perspective the long lasting history of the Pax Augusta also seems to silently convey a comparison with those who did not manage to accomplish the true gain for the Roman state, i.e. pax. This way also the Parthica signa recepta could recall his main political rival’s failure precisely and silently.